A meta-analysis of the relationship between public service motivation and individual job performance: cross-validating the effect of culture. Issue 7 (1st December 2022) - Fan, Yangyang; Blalock, Emily C.; Lyu, Xiaojun
Abstract: Although public service motivation (PSM) is an issue of global concern, there should be further exploration of the impact of the cross-cultural effect on PSM research. The current study conducted a meta-analytic examination on the relationship between PSM and individual job performance in a cross-cultural context. Based on 40 correlations in 34 separate studies among 12 countries/regions, the findings support the positive relationship between PSM and individual job performance. The relationship is more robust in cultures with higher power distance than the lower counterparts, and results were mutually verified by Hofstede's model and GLOBE model. Moreover, we found these effects differ across measurements of individual job performance but were more stable across the PSM measurements. The findings provide a clear explanation for the relationship between PSM and individual job performance from a cross-cultural perspective. The current study offers a cross-validating way of testing the effect of culture and also inspires practitioners in the domain of public administration.